On the Influence of Cavitation Volume Variations on Propeller Broadband Noise - Leonie S. Föhring; Peter Møller Juhl; Dietrich Wittekind (Journal of Marine Science and Engineering, 2022)
Low-frequency broadband shipping noise causes a growing concern for marine fauna together with the demand for noise reduction. Detailed analyses of the cavitation behaviour in the time domain serve as a prerequisite for steps toward quieter propellers. Underwater noise measurement data from the propeller of a full-scale container vessel are used for the analysis of the cavitation volume behaviour. Sequencing methods, polynomial models, and stochastic evaluation methods feeding Monte Carlo simulations of unsteady sheet cavitation are applied to identify the cause of an often observed, yet unexplained similarity in shipping noise spectra. Characteristic features of the volume evolution are identified to enhance the understanding of noise generation by sheet cavitation.